Strategi Pemasaran Digital dan Branding Rawon Premium By Salina Kitchen Melalui Instagram - Santi Rimadias; Wasi Bagasworo; Dina Dwi Marinda (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This community service program focused on enhancing branding and digital marketing strategies for Salina Kitchen, a culinary business in Jakarta. The primary objectives were to optimize packaging sticker design and to boost engagement through the business's Instagram account. Conducted from September 23 to December 15, 2023, the program involved consumer surveys and SWOT analysis. Results indicated a significant improvement in customer satisfaction with packaging design and digital marketing performance. Effective use of hashtags on Instagram expanded the reach to non-followers. The program successfully identified key strategies in branding and digital marketing that can be implemented to enhance the performance of culinary businesses.